2019
DOI: 10.1016/j.dnarep.2019.102698
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of stimulation of DNA binding of the transcription factors by human apurinic/apyrimidinic endonuclease 1, APE1

Abstract: HIGHLIGHTS-APE1 forms a stable complex with ssDNA longer than 15 mer; -APE1-catalyzed repair and TF-stimulating activities depend on the structure of DNA duplex; -APE1 acts synergistically with reducing agents to stimulate DNA binding of AP-1 and p50; -APE1 stimulates DNA binding of p50-C62S redox-insensitive mutant; -APE1 forms stable multiprotein oligomers on intrinsically curved DNA regions. ABBREVIATIONSROS, reactive oxygen species; AP, apurinic/apyrimidinic site; THF, 3-hydroxy-2hydroxymethyltetrahydrofur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 97 publications
3
18
0
Order By: Relevance
“…By contrast, this domain affects both the rate of formation and the stability of the initial complex in the cases of NIR and 3 →5 exonuclease activities (Gros et al, 2004;Daviet et al, 2007;Timofeyeva et al, 2009). Multiple studies also underscore that the N-terminal domain may functionally interact with different proteins involved in DNA repair (Kladova et al, 2018a;Moor et al, 2020;Popov et al, 2020), transcription (Georgiadis et al, 2008;Kelley et al, 2011;Bazlekowa-Karaban et al, 2019), and RNA metabolism (Vascotto et al, 2009;Tell et al, 2010;Poletto et al, 2013). Summarizing the literature data, we can conclude that the N-terminal domain may be required for the preliminary low-affinity binding process in search of the proper lesion in DNA or a cleavage site in RNA and proteinprotein interactions.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, this domain affects both the rate of formation and the stability of the initial complex in the cases of NIR and 3 →5 exonuclease activities (Gros et al, 2004;Daviet et al, 2007;Timofeyeva et al, 2009). Multiple studies also underscore that the N-terminal domain may functionally interact with different proteins involved in DNA repair (Kladova et al, 2018a;Moor et al, 2020;Popov et al, 2020), transcription (Georgiadis et al, 2008;Kelley et al, 2011;Bazlekowa-Karaban et al, 2019), and RNA metabolism (Vascotto et al, 2009;Tell et al, 2010;Poletto et al, 2013). Summarizing the literature data, we can conclude that the N-terminal domain may be required for the preliminary low-affinity binding process in search of the proper lesion in DNA or a cleavage site in RNA and proteinprotein interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Although earlier studies showed that in the middle-binding mode, APE1 can excise the mismatched 3′-end of a dsDNA substrate 20,24,25,37,38 , whether the physiologically more relevant matched dsDNA substrates are also vulnerable to the exonuclease activity of APE1 has not been established. Our results show that the matched dsDNA substrates can indeed be digested by mAPE1, albeit they have higher recalcitrance than the mismatched counterpart (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the gel, the band of protein-DNA complex similar to that in the aforementioned substrates is also observed. This band is rather smeared, though, reflecting the likelihood of more than one APE1 attaching to a dsDNA substrate in the case of terminal binding 37 . For the binding of mAPE1 with AP site-containing dsDNA and gapped dsDNA, on the other hand, an additional band for a lower molecular weight protein-DNA complex is observed at the lower protein concentration of 0.5 μM (Fig.…”
Section: Exonucleolytic Cleavage Of Ape1 Distinguishes Substrate Strumentioning
confidence: 99%
“…Recent observations brought forward a somewhat unexpected hypothesis that unifies all these functions under a model of APE1 multimerization on DNA. Transmission electron microscopy and atomic force microscopy revealed that the full-length APE1 can form filaments on both undamaged and damaged DNA fragments and introduce bends and kinks that can be used to detect an AP site [149,189]. Several APE1 molecules was observed to bind both undamaged and damaged oligonucleotides in an apparently cooperative mode, with single-stranded DNA or nicks acting as preferential binding sites [189].…”
Section: Ape1 and Tdg: Cooperative Mediators?mentioning
confidence: 99%